2020
DOI: 10.1111/jcmm.14772
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D3 promotes the cell proliferation by activating the ERK1/c‐MYC axis in breast cancer

Abstract: Breast cancer is the second leading death cause of cancer death for all women.Previous study suggested that Protein Kinase D3 (PRKD3) was involved in breast cancer progression. In addition, the protein level of PRKD3 in triple-negative breast adenocarcinoma was higher than that in normal breast tissue. However, the oncogenic mechanisms of PRKD3 in breast cancer is not fully investigated. Multi-omic data showed that ERK1/c-MYC axis was identified as a major pivot in PRKD3-mediated downstream pathways. Our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…As an important member of the Myc family, c-Myc is an oncogene in breast cancer [ 27 ]. It plays an important role in promoting the occurrence and development of tumours [ 28 ] and in promoting and maintaining tumour cell proliferation [ 29 ], differentiation, and apoptosis [ 30 ]. In recent years, a large number of studies have shown that c-Myc plays an important role in regulating the metabolism, proliferation, and apoptosis of TNBC cells [ 30 – 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an important member of the Myc family, c-Myc is an oncogene in breast cancer [ 27 ]. It plays an important role in promoting the occurrence and development of tumours [ 28 ] and in promoting and maintaining tumour cell proliferation [ 29 ], differentiation, and apoptosis [ 30 ]. In recent years, a large number of studies have shown that c-Myc plays an important role in regulating the metabolism, proliferation, and apoptosis of TNBC cells [ 30 – 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible mechanisms is that PRKD3 promotes TNBC cell proliferation via contributing to mammalian target of rapamycin complex 1/ribosomal protein S6 kinase B1 pathway activation 29 . Other researchers suggest that PRKD3 promotes the proliferation of breast cancer cells by activating the mitogen-activated protein kinase 3/MYC proto-oncogene axis or ELAV like RNA binding protein 1 32 , 33 . The RhoGEF GRF-H1 is claimed to activate PRKD3 for the maintenance of TNBC stem cells 34 .…”
Section: Oncogenic Functions Of Prkd3 In Breast Cancermentioning
confidence: 99%
“…Protein Kinase D (PKD) family members integrate multiple hormonal and metabolic signals to coordinate homeostasis of the organism (Kolczynska, Loza-Valdes et al, 2020, Löffler, Mayer et al, 2018, Rozengurt, 2011, Sumara, Formentini et al, 2009. The family of PKDs comprises three kinases: PKD1, PKD2, and PKD3 (Fu & Rubin, 2011, Rozengurt, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…PKD1 and PKD2 share the highest homology, while PKD3 kinase is the unique member of the family. PKD1 and PKD2 have been widely studied in different cellular processes such as trans-Golgi network dynamics, cell proliferation and cell migration, adipocytes function, insulin secretion as well as regulation of innate and adaptive immune cells function (Gehart, Goginashvili et al, 2012, Goginashvili, Zhang et al, 2015, Ittner, Block et al, 2012, Kolczynska et al, 2020, Löffler et al, 2018, Rozengurt, 2011, Sumara et al, 2009, Zhang, Meszaros et al, 2017. The specific functions of PKD3 are still relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation